The Deformation and Acoustic Emission of Aluminum-Magnesium Alloy under Non-Isothermal Thermo-Mechanical Loading; AIP Conference Proceedings; Vol. 1683 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures - Makarov S. V.; Plotnikov V. A.; Lysikov M. V.; Kolubaev Е. А. Evgeny Aleksandrovich (2015, 2015)
Title screen